Diabetes mellitus and its skin manifestations - dermatology for diabetologists - Maria Sambura; Sara Rosołowska-Żak; Julia Pałuchowska; Anna Szymkowicz; Patrycja Paschke; Igor Miczek (Kazimierz Wielki University, 2024)
Introduction: Diabetes Mellitus (DM) one of the most common chronic disease in Europe, can affect every part of the body including the skin. Metabolic changes during the progress of diabetes mellitus , influence the occurence of various dermatoses such as Acanthosis nigricans, Necrobiosis lipoidica diabeticorum, bullosis diabeticorum, eruptive xanthomatosis and diabetic dermopathy.  On the other hand, there are allergic skin reactions as a consequence of insulin infusion, diabetic pills treatment and using diabetic devices like insulin pumps and glucose monitors that can improve patiens glycemic control and their quality of life.    Aim of the study: The aim of our study is to present skin manifestations associated with diabetes mellitus patients. The importance of early detection skin changes and its significance are also analysed.    Material and methods: We searched electronic databases, using keywords such as "Diabetes Mellitus" , " Skin dermatoses assosiated with diabetes mellitus " and "Acanthosis Nigricans"    Conclusions: Human skin is a reflection of the processes that take place in the body. The characteristc dermatoses that appear on it, can be a clue for the doctor and help him in the diagnostic process and proper control of diabetes. Technological progress has led to the develompent of specialized devices to control the glycemia of patients, however, this is often associated with the deterioration in the well-being of patients and the benefits of treatment ,by reverse allergic skin reactions to contact with the equipment.